Radicalisation, counter-radicalisation and prevent: a vernacular approach - Jarvis, Lee (Manchester University Press, 2024)
This book offers the first sustained investigation into non-elite understandings of radicalisation and counter-radicalisation policy. Drawing on original focus group research with students from universities across England and Wales, the book explores how 'ordinary' citizens understand radicalisation, how they make sense of counter-radicalisation initiatives like the UK Prevent Strategy, and how they evaluate its functioning and effects across society. Radicalisation, counter-radicalisation and Prevent demonstrates that these non-elite insights often contradict and diverge from traditional (elite) security knowledge and thus shed new light on wider questions around the politics of security. This has vitally important implications not only for counter-radicalisation and counter-terrorism policy but for the very study and practice of security.